Dengue Encephalopathy or Japanese Encephalitis? Co-Infection or Serologic Cross- Reactivity? - Moh, Cheng Keat; Wong, Calvin Ke Wen; Ker, Hong Bee (Malaysian Journal of Medicine and Health Sciences, 2022)
Dengue infection has a wide clinical spectrum ranging from asymptomatic presentation to life-threatening severe dengue with multiorgan failure, and increasingly recognized neurological presentation in the past decade. Japanese encephalitis on the other hand is another common mosquitoes-borne flavivirus infection endemic in Southeast Asia, which share some similar clinical features. We report a case of a 38-year-old male patient who presented to us with complaints of fever and acute encephalitis syndrome with positive dengue NS1 antigen, and positive cerebrospinal fluid serologies for both dengue and JE immunoglobulins. Magnetic Resonance Imaging findings were suggestive of encephalitic changes. Co-infection and serology cross-reactivity of these two flaviviruses is not uncommon in countries where both dengue and Japanese encephalitis are endemic, and thus, the treating clinician should have a high index of suspicion if clinical and serological evidence are present whilst treating the patient.